Synthesis of Heteroaryl-Substituted Pyrroles via the 1,3-Dipolar Cycloaddition of Unsymmetrical Münchnones and Nitrovinylheterocycles - Lopchuk, Justin M.; Song, Mia; Butler, Blythe; Gribble, Gordon W. (Synthesis, 2015)
A series of furanyl-, thiophenyl-, and pyrrolo-substituted pyrroles were prepared via the 1,3-dipolar cycloaddition of unsymmetrical münchnones and nitrovinylheterocycles. The regiochemical outcome of the furan and thiophene cycloadditions compares favorably to previously reported cycloadditions with β-nitrostyrene, while the nitrovinylpyrrole cycloadditions mirror the results observed with nitrovinylindole.
Keywords: cycloaddition; heterocycles; pyrroles; regioselectivity; münchnone